Osteochondrosis of the distal aspect of the sagittal ridge of the third metacarpal bone in horses : a clinical, radiographic and arthroscopic description - Macedo, Maria da Conceição Líbano Monteiro da Costa (2024)
Dissertação de Mestrado Integrado em Medicina Veterinária, área científica de Clínica